Mass Balance of Austre Grønfjordbreen, Svalbard, 2006–2020, Estimated by Glaciological, Geodetic and Modeling Aproaches - Nelly Elagina; Stanislav Kutuzov; Ekaterina Rets; Andrei Smirnov; Robert Chernov; Ivan Lavrentiev; Bulat Mavlyudov (Geosciences, 2021)
Glacier mass balance measurements, reconstructions and modeling are the precondition for assessing glacier sensitivity to regional climatic fluctuations. This paper presents new glaciological and geodetic mass balance data of Austre Grønfjordbreen located in the western part of Nordenskiöld Land in Central Spitsbergen. The average annual mass balance from 2014 to 2019 was −1.59 m w.e. The geodetic mass balance from 2008 to 2017 was −1.34 m w.e. The mass balance was also reconstructed by the temperature-index model from 2006 to 2020 and by spatially-distributed energy-balance models for 2011–2015 and 2019. We found a cumulative mass balance of −21.62 m w.e. over 2006–2020. The calculated mass-balance sensitivity to temperature was −1.04 m w.e. °C−1, which corresponds to the highest glacier mass balance sensitivity among Svalbard glaciers. Sensitivity to precipitation change was 0.10 m w.e. for a 10% increase in precipitation throughout the balance year. Comparing the results of the current study with other glacier mass balance assessments in Svalbard, we found that Austre Grønfjordbreen loses mass most rapidly due to its location, which is mostly influenced by the warm West Spitsbergen Current, small area and low elevation range.